Pembentukan Karakter Religius Siswa Melalui Kegiatan Pembiasaan di SMP PGII 2 Bandung - yayat hidayat; Nan Rahminawati; Eko Surbiantoro (Bandung Conference Series: Islamic Education, 2023)
Abstract. The purpose of this research is (1) to find the basis for implementing habituation activities at SMP PGII 2 Bandung (2) to identify planning, implementation and evaluation of habituation activities in the context of forming religious character at SMP PGII 2 Bandung (3) to explore the impact of implementing habituation activities on character, religious attitudes and actions of students in SMP PGII 2 Bandung. This research is an empirical research using a qualitative descriptive approach. Data collection techniques in this research are using the methods of observation, interviews, and documentation studies. This qualitative research uses theoretical and empirical activities presented in the form of narrative texts to clearly explain the basis for implementing habituation activities, planning, implementing and evaluating habituation activities, as well as the impact of implementing habituation activities on the character, attitudes and religious actions of students in SMP PGII 2 Bandung. The results of this study are (a) The basis for habituation activities at SMP PGII 2 Bandung is made at the policy of the Education Foundation and has been stated in the school's vision and mission. (b) Planning for habituation activities at SMP PGII 2 Bandung is carried out at the beginning of the semester by the student curriculum together with the principal including planning for chanting Asmaul Husna, tadarus together, tausiyah about aqidah, morality, and worship, as well as dhuha prayers and fasting Monday-Thursday. (c) Habituation activities on religious characters produce a positive impact because students become obedient in practicing worship and apply it slowly to become habitual within themselves so that religious values ​​are attached to students. Abstrak. Tujuan dari penelitian ini adalah (1) Menemukan landasan pelaksanaan kegiatan pembiasaan di SMP PGII 2 Bandung (2) Mengidentifikasi perencanaan, pelasanaan dan evaluasi kegiatan pembiasaan dalam rangka pembentukan karater religius di SMP PGII 2 Bandung (3) Mendalami dampak pelaksanaan kegiatan pembiasaan terhadap karakter, sikap dan perbuatan religius siswa di SMP PGII 2 Bandung. Penelitian ini merupakan penelitian empirik dengan menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data dalam peneltian ini yaitu menggunakan metode observasi, wawancara, dan studi dokumentasi. Penelitian kualitatif ini menggunakan kegiatan secara teoritis dan empiris yang disajikan dalam bentuk teks naratif untuk memaparkan secara jelas mengenai landasan pelaksanaan kegiatan pembiasaan, perencanaan, pelasanaan dan evaluasi kegiatan pembiasaan, serta dampak pelaksanaan kegiatan pembiasaan terhadap karakter, sikap dan perbuatan religius siswa di SMP PGII 2 Bandung. Hasil dari penelitian ini yaitu (a) Landasan kegiatan pembiasaan di SMP PGII 2 Bandung dibuat atas kebijakan dari Yayasan Pendidikan dan telah tertuang dalam visi dan misi sekolah. (b) Perencanaan kegiatan pembiasaan di SMP PGII 2 Bandung dilakukan pada awal semester oleh bidang kesiswaan kurikulum bersama dengan kepsek meliputi perencanaan pelantunan asmaul husna, tadarus bersama, tausiyah tentang aqidah, akhlaq, dan ibadah, serta sholat dhuha dan puasa senin-kamis (c) Kegiatan pembiasaan terhadap karakter religious menghasilkan dampak yang positif sebab peserta didik menjadi taat dalam mengamalkan ibadah dan menerapkannya secara perlahan menjadi pembiasaan dalam diri sendiri sehingga nilai religious melekat pada peserta didik.